GENE-53. IDENTIFICATION OF EPITHELIAL MEMBRANE PROTEIN 2 (EMP2) AS A MOLECULAR MARKER AND THERAPEUTIC TARGET IN MENINGIOMA. (11th November 2019) - Patel, Kunal; Duong, Courtney; Sun, Matthew; Romiyo, Prasanth; Kejriwal, Sameer; Chan, Ann; Gordon, Lynn; Wadehra, Madhuri; Yang, Isaac
Abstract: BACKGROUND: Intracranial meningiomas have been associated with a heterogenous set of genetic and molecular alterations. Despite these genetic associations, targeted therapies have been unable to increase survival in recurrent or residual meningiomas. There is a need for identification of therapeutic targets in meningioma. MATERIALS & METHODS: Normal brain tissue from routine autopsy and tumor specimens from patients undergoing primary surgical resection of meningioma were analyzed. Pathologic diagnosis and grade were identified. Samples were stained with anti-EMP2 antisera and visualized with DAB (3, 3'-Diaminobenzidine). Western blot analysis was carried out RESULTS: In 17 patients with meningioma, there was statistically significant EMP2 staining in fresh brain tumor samples. EMP2 expression was confirmed and quantified with western blot which demonstrated significant positive expressivity. There were 12 grade I, 4 grade II, and 1 grade III meningiomas in our dataset and a significant trend towards increased EMP2 expression with higher grade. EMP2 expression was not identified in normal brain tissue samples from different locations including gray matter, white matter, and meninges in 3 control patients. CONCLUSIONS: EMP2 is a protein associated with cell migration, invasion, and angiogenesis not identified in normal brain tissue but found in meningioma. EMP2 expression may be associated with increased tumor invasion and is a potential therapeutic target for residual or recurrent meningioma.